Formation and dispersion of toxic combustion byproducts from small-scale combustion systems - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
Pollutants of primary interest are SOx, CO, NOx, methane and other volatile organics, and particulate matter. First- and second-law efficiencies have been evaluated. Next, the turbulent flows of exhaust gases through the stack have been modeled for both natural draft stacks and stacks equipped with forced draft fans. Velocity and temperature profiles in the stacks and for the plumes have been obtained from the numerical model for specified meteorological conditions. (C) 1997 Elsevier Science Ltd.
Keywords: FUEL